Epistemologi Ilmu dalam Filsafat Pendidikan Islam - Endah Durrotul Jannah; Putri Nurkhasanah; Muhammad Syafa Atur Rizki (Pascasarjana Universitas PGRI Semarang, 2026)
Epistemology in Islamic educational philosophy is a study that examines the nature, sources, and methods of acquiring knowledge based on revelation, reason, and empirical experience. This study aims to examine the concept of epistemology from the perspective of Islamic educational philosophy and its relevance to the development of educational systems in the modern era. The method used in this study is qualitative research with a literature study approach through analysis of various sources related to epistemology and Islamic education. The results indicate that Islamic educational epistemology positions the Qur'an and Hadith as the primary sources of knowledge, combined with reason and empirical experience. Furthermore, this epistemology emphasizes the integration of religious and general knowledge and the balance between intellectual, spiritual, and moral aspects in developing knowledgeable, faithful, and noble individuals.